2010
DOI: 10.1007/s10661-010-1597-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of pesticide residues in market basket samples of vegetable from Lucknow City, India: QuEChERS method

Abstract: The study was conducted on 20 vegetables including leafy, root, modified stem, and fruity vegetables like bitter gourd, jack fruit, french-bean, onion, colocassia, pointed gourd, capsicum, spinach, potato, fenugreek seeds, carrot, radish, cucumber, beetroot, brinjal, cauliflower, cabbage, tomato, okra, and bottle gourd. Forty-eight pesticides including 13 organochlorines (OCs), 17 organophosphates (OPs), 10 synthetic pyrethriods (SPs), and eight herbicides (H) pesticides were analyzed. A total number of 60 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
5
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 22 publications
(16 reference statements)
0
33
5
2
Order By: Relevance
“…In the present study the pH of water samples varied from 7.60 to 8.72. The highest level of pH recorded in Ukkadam Lake was 8.72 which exceed the permissible limits (6.5-8.5).The pH levels in the water in Ukkadam Lake were mostly higher than the previous reports 13 .Dissolved oxygen levels in lakes vary according to their trophic levels, and depletion of DO in water probably is the most frequent result of water pollution 14 . It fluctuates seasonally and also daily with variations in water temperatures mainly due to consumption of DO owing to respiration by aquatic animals, decomposition of organic matter, and various chemical reactions [15][16] .…”
Section: Results and Discussion Ph Dissolved Oxygen And Faecal Coliformmentioning
confidence: 68%
“…In the present study the pH of water samples varied from 7.60 to 8.72. The highest level of pH recorded in Ukkadam Lake was 8.72 which exceed the permissible limits (6.5-8.5).The pH levels in the water in Ukkadam Lake were mostly higher than the previous reports 13 .Dissolved oxygen levels in lakes vary according to their trophic levels, and depletion of DO in water probably is the most frequent result of water pollution 14 . It fluctuates seasonally and also daily with variations in water temperatures mainly due to consumption of DO owing to respiration by aquatic animals, decomposition of organic matter, and various chemical reactions [15][16] .…”
Section: Results and Discussion Ph Dissolved Oxygen And Faecal Coliformmentioning
confidence: 68%
“…These pesticides can persist on cabbage for long period of time as they are not affected by the environmental conditions (Abo-El-Seoud et al 1995;Ripley et al 2001). When pesticide residues were monitored on different vegetable crops, the maximum residues were detected in cabbage (Srivastava et al 2011;Lozowicka et al 2012). Therefore, it is essential to study the persistence of pesticide residues on cabbage, whenever it is applied for crop protection.…”
Section: Introductionmentioning
confidence: 99%
“…In India most report concerning on organochlorine pesticide analysis in food samples (Bhanti, Shukla & Taneja 2004;Bhanti & Taneja 2005;Kumari, Kumar & Kathpal 2001;Mandal & Singh 2010;Sharma, Nagpal, Pakade & Katnoria 2010) and few studies have been reported on the measurement of OP pesticides in food samples (Srivastava, Trivedi, Srivastava, Lohani, & Srivastava, 2011).…”
Section: Introductionmentioning
confidence: 99%